Effect of White Guava (Psidium guajava L.) Fruit Puree in Rats Injected with 2,4,5,6(1H,3H)-Pyrimidinetetrone: Treatment of Diabetic Mellitas by Extract of White Guava Fruit Puree - Victor Eshu Okpashi; Kate Mlumun Ucho; Emmanuella Ekpenyong-Anwan Oyo-Ita; Bridget Bassey Jones (Biological Sciences - PJSIR, 2023)
There is a concern about finding alternate herbs for diabetic mellitus dysregulation. A focus on herbal treatments with proven anti-diabetic properties is being investigated. The effects of white guava fruit puree on diabetic Mellitus and its ability to protect hepatocytes in rats injected with 2,4,5,6(1H,3H)- pyrimidinetetrone were studied. The screening of qualitative phytochemicals in white guava fruit puree was done. The puree was tested for acute and sub-acute toxicity in mice at a dose of 5000 mg/Kg body weight. In different amounts, flavonoids, steroids, alkaloids, tannins, terpenoids, glycosides, saponins, reducing sugar and soluble carbohydrates were found. Resins and proteins were found to be undetectable. For twenty-one (21) days, rats were given 200 and 400 mg/Kg b.w of white guava fruit puree, where a significant (P::0.05) reduction in body weight was seen. There was a decrease in fasting and randomized blood glucose levels. They had reduced serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphates activities (ALP), which was suggestive (P::0.05). Non-diabetic rats were matched with diabetic rats given 200 and 400 mg/Kg b.w of white guava fruit puree. The results show that white guava fruit puree extract is both safe and effective in the treatment of diabetic Mellitus.